2020
DOI: 10.1111/acel.13287
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral inflammation preceeding ischemia impairs neuronal survival through mechanisms involving miR‐127 in aged animals

Abstract: Ischemic stroke, the third leading cause of death in the Western world, affects mainly the elderly and is strongly associated with comorbid conditions such as atherosclerosis or diabetes, which are pathologically characterized by increased inflammation and are known to influence the outcome of stroke. Stroke incidence peaks during influenza seasons, and patients suffering from infections such as pneumonia prior to stroke exhibit a worse stroke outcome. Earlier studies have shown that comorbidities aggravate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…This implies that miR-127 functions as an activator of cell differentiation and a suppressor of cell proliferation. Interestingly, the expression levels of miR-127 were also downregulated in the brains of aged mice, implying that miR-127 contributes to age-related defects or diseases [ 116 ]. Although not many studies have explored the function of miR-434-3p, it has been recently reported that circulating miRNA levels are decreased in patients with sarcopenia accompanied by chronic heart failure [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…This implies that miR-127 functions as an activator of cell differentiation and a suppressor of cell proliferation. Interestingly, the expression levels of miR-127 were also downregulated in the brains of aged mice, implying that miR-127 contributes to age-related defects or diseases [ 116 ]. Although not many studies have explored the function of miR-434-3p, it has been recently reported that circulating miRNA levels are decreased in patients with sarcopenia accompanied by chronic heart failure [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further processing, in all cases from -5p arm, give rise to two mature miR-7 sequences (miR-7a and miR-7b), differing only by a single nucleotide in the non-seed position number 10 (Figure 2C). To study the expression of the three miR-7 loci in our system, we utilized Global runon sequencing (GRO-seq), which enable the capture of nuclear nascent RNA primary molecules, and compared the expression in our murine culture 22 with different mouse tissues and cell lines [22][23][24][25][26][27][28][29][30][31][32] (Supplementary Table S3). In physiological conditions, only cortical neurons and the pituitary gland actively transcribe all three independently regulated miR-7 loci (Figure 2D, Supplementary figure S3).…”
Section: Cirs-7 Network Is Altered In Conditions Mimicking Ischemic S...mentioning
confidence: 99%
“…Proteasomal activity decreases during normal aging and in neurodegeneration [ 80 ]. Within the last year, two studies have described the contribution of miRNA regulation on UPS-related alterations throughout aging in the non-disease context [ 81 , 82 , 83 ]. For example, miR-127-5p was found to have reduced expression in the brains of aged C57BL/6J mice undergoing LPS-induced ischemia, and for the first time, identified 26S proteasome non-ATPase regulatory subunit 3 (Psmd3) as one of its targets [ 82 ].…”
Section: Mirnas Mediate the Ubiquitin-proteosome System In Brain Agin...mentioning
confidence: 99%
“…Within the last year, two studies have described the contribution of miRNA regulation on UPS-related alterations throughout aging in the non-disease context [ 81 , 82 , 83 ]. For example, miR-127-5p was found to have reduced expression in the brains of aged C57BL/6J mice undergoing LPS-induced ischemia, and for the first time, identified 26S proteasome non-ATPase regulatory subunit 3 (Psmd3) as one of its targets [ 82 ]. This study is important because the authors not only provided a brain miRNome through mature miRNA sequencing but also identified a novel miRNA in the brain, miR-127, which is associated with cell apoptosis and proteasomal activity during aging and ischemia.…”
Section: Mirnas Mediate the Ubiquitin-proteosome System In Brain Agin...mentioning
confidence: 99%